The effects of restricted energy and fluid intake on simulated amateur boxing performance - Smith, M.; Dyson, R.; Hale, T.; Hamilton, M.; Kelly, J.; Wellington, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
This study examined the effects of serial reductions in energy and fluid intake on two simulated boxing performances separated by 2 days recovery. Eight amateur boxers (age: 23.6 ± 3.2 years; height 175 ± 5 cm; body mass [BM] 73.3 ± 8.3 kg [Mean ± SD]) performed two simulated boxing bouts (BB) under normal (N-trial) and restricted (R-trial) diets in a counterbalanced design over 5 days. The trials were separated by a 9-day period of normal dietary behavior (X-trial). BM was recorded on days 1, 3, and 5 of each trial. Simulated bouts of three, 3-min rounds with 1-min recovery were completed on days 3 (BB1) and 5 (BB2) of each 5-day trial. Punching force (N) was recorded from 8 sets of 7 punches by a purpose-built boxing ergometer. Heart rate (fC) was monitored continuously (PE3000 Polar Sports Tester, Kempele, Finland), and blood lactate (BLa) and glucose (BG) were determined 4-min post-performance (2300 StaPlus, YSI, Ohio). Energy and fluid intakes were significantly lower in the R-trial (p < .05). Body mass was maintained during the N-trial but fell 3% (p < .05) during the R-trial. There were no significant differences in end-of-bout fC or post-bout BG, but BLa was higher in the N- than the R-trial (p < .05). R-trial punching forces were 3.2% and 4.6% lower, respectively, compared to the corresponding N-trial bouts, but the differences did not reach statistical significance. These results suggest that energy and fluid restrictions in weight-governed sports do not always lead to a significant decrease in performance, but because of the small sample size and big variations in individual performances, these findings should be interpreted with care.